A 3D printed plastic frame deeply impacts yeast cell growth - Molina-Menor, Esther; Vidal-Verdú, Àngela; Gomis-Olcina, Carlos; Peretó, Juli; Porcar, Manuel (Frontiers in Bioengineering and Biotechnology, 2023)
Solid State Fermentation (SSF) processes have been explored for yeast growth and protein and metabolites production. However, most of these processes lack standardization. In this work, we present a polylactic acid (PLA) 3D printed matrix that dramatically enhances yeast growth when embedded in liquid media compared to equivalent static cultures, and changes yeast expression patterns at the proteome level (data are available via ProteomeXchange with identifier PXD043759). Moreover, differences in sugar assimilation and ethanol production, as the main product of alcoholic fermentation, are observed. Our results suggest that these matrixes may be useful for a vast range of biotechnological applications based on yeast fermentation.